2021
DOI: 10.3390/ijms222312845
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Immunofluorescent Detection of the PRAME Antigen Using a Practical Antibody Conjugation Approach

Abstract: Bioconjugation of antibodies with various payloads has diverse applications across various fields, including drug delivery and targeted imaging techniques. Fluorescent immunoconjugates provide a promising tool for cancer diagnostics due to their high brightness, specificity, stability and target affinity. Fluorescent antibodies are widely used in flow cytometry for fast and sensitive identification and collection of cells expressing the target surface antigen. Nonetheless, current approaches to fluorescent lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Dichloromethane (DCM) and methanol (MeOH) were purified by distillation, dimethyl sulfoxide (DMSO) was purified by vacuum distillation and stored over 3 Å molecular sieves. Compounds 4 [ 35 ], 15 [ 56 ], 19 [ 35 ], 20 [ 57 ], 23 [ 58 ], 26 [ 57 ], 28 [ 31 ], and 29 [ 56 ] were prepared as described previously. Yields refer to chromatographically and spectroscopically ( 1 H and 13 C NMR) homogeneous materials, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dichloromethane (DCM) and methanol (MeOH) were purified by distillation, dimethyl sulfoxide (DMSO) was purified by vacuum distillation and stored over 3 Å molecular sieves. Compounds 4 [ 35 ], 15 [ 56 ], 19 [ 35 ], 20 [ 57 ], 23 [ 58 ], 26 [ 57 ], 28 [ 31 ], and 29 [ 56 ] were prepared as described previously. Yields refer to chromatographically and spectroscopically ( 1 H and 13 C NMR) homogeneous materials, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…However, the high reactivity of oxyamines even in salt form reduces the panel of available reagents. Recently, we found that the 1-ethoxyethylidene-protecting group on oxyamines allows for performing oxime ligation on periodate-oxidized IgG in situ in an acidic acetate buffer with pH 3.6, with such protected oxyamine derivatives of fluorescent dyes having a virtually unlimited shelf lifetime [ 31 ]. These findings prompted us to apply protected dye oxyamines to the ADC technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach involves directly conjugating the target molecule with the antibody in one step, eliminating the need for additional procedures (Figure 22). Antibody conjugates with dyes [137,216,232,254,255], cytotoxic drugs such as auristatins [169,221,241,243,256,257] and pyrrolobenzodiazepines [220], folic acid [258], PSMA (prostate-specific membrane antigen) ligands [242], and LXR (liver X receptor) agonists [259] have been generated using this approach. In addition, numerous antibody conjugates with oligonucleotides have been developed, demonstrating the versatility of this method [238][239][240]260] (Figure 23).…”
Section: Conjugates: Modification Of the Carbonyl Groupmentioning
confidence: 99%